Thoracic aortic disease in patients with heterozygous variants outside the central region of FBN2 - Demal, Till Joscha; Sachse, Marco; Metzlaff, Celia; Schüler, Helke; Szöcs, Katalin; Olfe, Jakob; Stark, Veronika; Frommolt, Peter; von Kodolitsch, Yskert; Mir, Thomas S.; Rybczynski, Meike; Reichenspurner, Hermann; et al. (Circulation. Genomic and precision medicine, 2025)
BACKGROUND: - Heterozygous pathogenic variants in the central region (exon 23-34) of FBN2 cause a hereditary connective tissue disorder named congenital contractural arachnodactyly, which presents with obligatory skeletal features but rarely with vascular manifestations. Scarce data exist on the association between FBN2 variants and aortic disease. This study aimed to investigate whether the location of FBN2 variants correlates with distinct clinical features, including aortic disease. - METHODS: - In this case-controlled cohort study, we ascertained clinical features, sequenced 62 (candidate) disease genes, and classified variants according to the American College of Medical Genetics and Genomics/Association for Molecular Pathology guidelines in 392 patients with suspected connective tissue or thoracic aortic diseases. We summarized our results and published data and compared clinical manifestations between patients with variants outside and within the central region of FBN2. - RESULTS: - Heterozygous FBN2 variants outside the central region were identified in 10 patients from 5 families. Two variants were of uncertain significance, 1 was likely pathogenic, and 2 were pathogenic. A total of 60% of these patients had thoracic aortic disease, but only 20% were diagnosed with congenital contractural arachnodactyly according to an established clinical scoring system. Combined data from the literature and this study revealed that patients with FBN2 variants outside the central region presented with aortic dilatation (55.0% versus 9.9%; P<0.001) more often and had less pronounced musculoskeletal manifestations (congenital contractural arachnodactyly score, 5.6±5.1 versus 9.8±3.6; P=0.011) compared with those with central region variants. - CONCLUSIONS: - Our results suggest that heterozygous FBN2 variants outside the central region predispose individuals to thoracic aortic disease and are less associated with the typical clinical presentation of congenital contractural arachnodactyly than pathogenic variants in the FBN2 central region.
Gesehen am 25.09.2025